Competing with precision: incentives for developing predictive biomarker tests - Brekke, Kurt R. (2022)
We study the incentives of drug producers to develop predictive biomarkers, taking into account strategic interaction between drug producers and health plans.For this purpose we develop a two-dimensional spatial frame work that allows us to capture the informational role of biomarkers and their effects on price competition and treatment choices. Although biomarkers increase the information available to prescribers, we identify an anticompetitive effect on the prices set by producers of therapeutically substitutable drugs. We also find that better information about each patient's most therapeutically appropriate drug does not necessarily lead to more efficient treatment outcomes.